Highly efficient Meerwein–Ponndorf–Verley reductions over a robust zirconium-organoboronic acid hybrid. Issue 3 (25th January 2021) - Song, Jinliang; Hua, Manli; Huang, Xin; Visa, Aurelia; Wu, Tianbin; Fan, Honglei; Hou, Minqiang; Zhang, Zhaofu; Han, Buxing
Abstract : Synergetic effect of Zr 4+ and borate in zirconium organoborate could significantly promote the Meerwein–Ponndorf–Verley reduction of various biomass-based carbonyl compounds. Abstract : The Meerwein–Ponndorf–Verley (MPV) reaction is an attractive approach to selectively reduce carbonyl groups, and the design of advanced catalysts is the key for these kinds of interesting reactions. Herein, we fabricated a novel zirconium organoborate using 1, 4-benzenediboronic acid (BDB) as the precursor for MPV reduction. The prepared Zr-BDB had excellent catalytic performance for the MPV reduction of various biomass-derived carbonyl compounds ( i.e., levulinate esters, aldehydes and ketones). More importantly, the number of borate groups on the ligands significantly affected the catalytic activity of the Zr-organic ligand hybrids, owing to the activation role of borate groups on hydroxyl groups in the hydrogen source. Detailed investigations revealed that the excellent performance of Zr-BDB was contributed by the synergetic effect of Zr 4+ and borate. Notably, this is the first work to enhance the activity of Zr-based catalysts in MPV reactions using borate groups.